The impact of changes in spatial development on microclimate conditions and thermal comfort: the example of Manufaktura in Łódź - Bochenek, Anna Dominika; Klemm, Katarzyna; Szulc, Amanda (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
The paper presents the impact of changes in spatial development on microclimate parameters and thermal comfort. The research area covers the site of the current shopping and service centre Manufaktura in Łódź, located in the former factory complex of Izrael Poznański. Analyses were carried out for the area before and after the revitalisation process. The transformations of the building structure, reductions in green areas, and modifications of the surface were highlighted. Three-dimensional terrain models were prepared, and simulations were conducted using the ENVI-met program. The influence of development transformations on thermal comfort and microclimate was assessed. Due to the negative impact of the changes, adaptive solutions were proposed. The data obtained showed a positive influence of the implemented blue-green strategies on thermal conditions and the microclimate.